2007
DOI: 10.1029/2006jd007064
|View full text |Cite
|
Sign up to set email alerts
|

Ozone loss driven by nitrogen oxides and triggered by stratospheric warmings can outweigh the effect of halogens

Abstract: Ozone loss in the lower and middle stratosphere in spring and summer, in particular over polar regions, is driven mainly by halogens and nitrogen oxides (NOx). Whereas the stratospheric chlorine levels are expected to decrease in the future, the role of NOx for the O3 budget in a changing climate is not well quantified. Here we combine satellite measurements and model simulations to diagnose the accumulated O3 loss during winter and spring 2002–2003 in the Arctic polar stratosphere. We show that in a winter st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
65
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(77 citation statements)
references
References 53 publications
(68 reference statements)
12
65
0
Order By: Relevance
“…The occurrence of major mid-winter SSW and the attending warmer temperature in the lower stratosphere are common to those winters. Similar ozone decreases are seen in previous studies, e.g., Sonkaew et al (2013), Kuttippurath et al (2010) and Konopka et al (2007). NO x photochemistry has 5 been suggested to be important for ozone loss in this altitude range (Osterman et al, 1997) .…”
supporting
confidence: 75%
See 1 more Smart Citation
“…The occurrence of major mid-winter SSW and the attending warmer temperature in the lower stratosphere are common to those winters. Similar ozone decreases are seen in previous studies, e.g., Sonkaew et al (2013), Kuttippurath et al (2010) and Konopka et al (2007). NO x photochemistry has 5 been suggested to be important for ozone loss in this altitude range (Osterman et al, 1997) .…”
supporting
confidence: 75%
“…However Konopka et al (2007) showed that,above 600 K (∼ 24 km), the chemical loss induced by the horizontal transport of NO x from lower latitudes is as great as the halogen-induced loss below 500 K (∼ 20 km) in the Northern Hemisphere in 2002/2003. In this paper we have extended the vertical analysis region up to PT of 950 K (∼ 40 km) in order to show the effect of NO x 5 transport on ozone losses. This paper contains the following sections.…”
mentioning
confidence: 99%
“…The continuous intrusion of NO x , reaching up to 100 ppbv in the upper stratosphere, led, via formation of N 2 O 5 and water ion cluster chemistry, to the formation of a second HNO 3 maximum at altitudes between 35 and 45 km with maximum vmrs of 14 ppbv . Although downward transport of mesospheric air as low down as 25 km also happened in the Arctic winter 2002/2003, the deposition of NO x rich air was considerably lower during this winter Konopka et al, 2007). This was due to a major stratospheric warming in midwinter which interrupted the downward transport, diluted the vortex air into midlatitudes, and led to conditions without significant subsidence afterwards.…”
Section: Properties Of Polar Stratospheric Cloudsmentioning
confidence: 96%
“…ECMWF temperature fields, however, indicate that regions with temperature low enough to sustain polar stratospheric clouds were smaller than in the 2002/2003 and 2004/2005 winters. Ozone loss driven by NO x chemistry [Konopka et al, 2007], is one possible cause for the ozone loss inferred on the 575 K potential temperature level at the end of the winter. To determine the full consequences of the 2007 Arctic ozone depletion for the northern hemisphere it would furthermore be necessary to study regions below the 475 K potential temperature level which is near the lowest level ($450 K) for reliable Odin/SMR 501.5 GHz ozone data.…”
Section: Summary and Discussionmentioning
confidence: 99%